Audit committee of cooperatives in Malaysia: level of competency / Yusri Huzaimi Mat Jusoh and Noor Marini Abdullah - Mat Jusoh, Yusri Huzaimi; Abdullah, Noor Marini (2018)
This study investigated the level of competency amongst audit committees (ACs) of Malaysian cooperatives (coops). AC competency (with proxies of educational background and accounting knowledge) has emerged as a significant theme in corporate governance debates. AC that possesses accounting knowledge is associated with effective monitoring. As such, this study employed 384 AC members as respondents representing large-, medium-, and small-sized coops. As a result, this study revealed that only 12.7 % of ACs held first degree, while almost half of them only possessed secondary level of education. In terms of accounting knowledge, only 10.1 % of the AC members possessed professional knowledge related to the abilities of analysing and issuing opinions on financial reporting, as well as providing added value to coops. Besides, only 5.2 % of the ACs fell under the technical level, which is associated with the ability to prepare and to understand financial reports, but not to the extent of analysing them. Meanwhile, 29.7% of the AC members had intermediate knowledge linked with the capability of preparing reports in accordance to specific format without the ability to comprehend them. Surprisingly, 23.4 % of the AC members were novice, hence lacked knowledge in accounting.